Response to comment on "Cathepsin-l influences the expression of extracellular matrix in lymphoid organs and plays a role in the regulation of thymic output and of peripheral T cell number" - Lombardi, María Gabriela (2006)
In our article published in The Journal of Immunology in June 1, 2005 (1), we reported that lymph nodes from nackt mice (CTSLnkt/CTSLnkt) are hypertrophied, showing a normal absolute number of CD4+ T cells and a marked increase in the number of CD8+ T lymphocytes. Correlatively, extracellular matrix (ECM) components were found to be increased. Contrarily, in nackt thymus, laminin, fibronectin, and collagen I and IV are markedly decreased, with an augmented output of CD8+ cells.